FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA INSPEKTORAT SEBAGAI AUDITOR PEMERINTAH (STUDI EMPIRIS PADA KANTOR INSPEKTORAT KOTA DAN KABUPATEN MADIUN) - Handayani, Dwi (Widya Warta, 2016)
The purpose of this study is to obtain empirical evidence regarding (1) the influence of competence, motivation and role suitability toward organizational commitment and (2) the influence of competence, motivation, role suitability and organizational commitment toward the performance of the government internal auditors. The unit of analysis is the behavior of the inspectorate internal auditors / employees. The population of this research is all the Madiun Municipality and Madiun Regency inspectorate officers who participate in regular inspection. While, the sample taken is 35 auditors. The data were obtained through questionaires directly distributed to the respondents. Variables in this research are competence, motivation, role suitability, organizational commitment and performance of the government internal auditors. The data were analyzed using SEM (Structural Equation Modeling) with the PLS ver 2.0. The results showed that (1) competence and role suitability did not influence organizational commitment, (2) motivation influenced organizational commitment, (3) competence, motivation and organizational commitment did not influence the performance of the government internal auditors, and (4) role suitability did not influence the performance of the government internal auditors.